Impact of the COVID-19 lockdown on the epidemiologic and clinic profiles of domestic accidents in children - Zineb Benmassaoud; Fatoumata Binta Balde; Zineb Oudghiri; Mohammed Tazi Charki; Hicham Abdellaoui; Karima Atarraf; My Abderrahmane Afifi (Wolters Kluwer Medknow Publications, 2022)
Background: Domestic accident (DA) is any harmful accidental event that occurs suddenly in the home or its immediate surroundings. Our study aims to describe the impact of the COVID-19 lockdown in the epidemiological and clinical profiles of DAs in children and their management. Materials and Methods: This was a mixed descriptive study, comparing DAs occurring during the COVID-19 lockdown and the same period of the previous year. We exhaustively included all children aged from 0 to 15 years admitted for DAs. Results: The incidence of DAs remains above 50% in both groups. The average age was 7 years and boys were more affected. Before the COVID-19 lockdown, the most common mechanism encountered was accidents on the public highway 20.75%, while during the lockdown, it was represented by falls from a high place with a height of 2 m or more. During the lockdown, 33.86% of patients consulted after more than 24 h of the trauma. Supracondylar fractures and burns remained the most frequent. In all cases, the cumulative frequency of fractures decreased during the lockdown. The COVID-19 lockdown had no impact on patient's management. Conclusion: The COVID-19 lockdown has negatively increased the consultation delay. However, it has considerably reduced the incidence of fractures.